Experimental investigation of the effect of LiBr on the high-pressure part of a ternary working fluid ammonia absorption refrigeration system. (5th March 2021) - Xu, Mengkai; Li, Shuhong; Jin, Zhenghao; Jiang, Weixue; Du, Kai
Highlights: The optimum lithium bromide concentration is 15% in ternary working fluid ammonia absorption refrigeration system. The cooling water mass flow in rectifier can be reduced to 44.9% of the requirement in low concentration. The rectification cooling load accounts for as low as 16% of the heating load. The heat in the outlet stream of generator can be recovery more sufficiently in solution heat exchanger. The generation pressure decreases with the application of LiBr because of the reduction of condenser cooling load. Abstract: This paper experimentally studies the influence of lithium bromide concentration on the coefficient of performance (COP) and other operating parameters in the high-pressure part of a ternary working fluid ammonia-water absorption refrigeration system. The lithium bromide concentrations in the ternary working fluid were 5%, 10%, 15%, and 20%. The lithium bromide concentration is the ratio of the mass of lithium bromide and the sum mass of lithium bromide and water. The generation temperature ranged from 100 °C to 130 °C, evaporation temperature was −10 °C, and the cooling water temperature was 28 °C. The experiment results show that 15% is the optimum lithium bromide concentration, and the highest COP is 0.408 when the generation temperature was 130 °C, which is 7.2% higher than AARS with binary working fluid. The COP improved because of the reduction of rectification cooling load, heat recovery, and operating pressure. The cooling water mass flows in the reflux condenser were reduced when applying lithium bromide in the working fluid, and the rectification cooling load decreases as low as 16% of the heating load in the generator. The heat recovery in the solution heat exchanger is too large after using ternary working fluid because the heat transfer coefficient of the ternary solution rises. Moreover, the generation pressure is related to the condensing temperature rather than lithium bromide concentration. Generally, AARS operates more efficiently, and the main components can be miniaturized with the application of ammonia-water-lithium bromide ternary working fluid.